Can Working Memory Strategies Enhance English Vocabulary Learning? - Diana Ibarra Santacruz (HOW, 2018)
This study sought to determine how working memory training could contribute to retaining vocabulary studied in English lessons through the implementation of a set of strategies. Two intact groups of beginners: one experimental, with 28 students, and one control group, with 22 students, belonging to undergraduate English as a foreign language courses at a Colombian university were involved in the study. After being exposed to a series of memory strategies for a period of 10 weeks, it was evident that most learners in the experimental group benefited from the intervention and showed gradual progress in the retention and retrieval of the words studied in the lessons; thus, improving their overall competence in the foreign language.